Relevance of the ancient Indian curriculum and pedagogic approaches in the present context with reference to NEP 2020 - Yadav, Nikita (S&Co Publishing, 2025)
The current study's goal is to examine, using relevant literature critically, the curricula and pedagogical practices used in ancient India and, as a result, determine their applicability in the current NEP 2020 framework. Research questions about curriculum analysis, pedagogical approaches, their applicability in NEP 2020, and the difficulties that may arise from putting them into practice were formulated based on the objectives. The study is analytical in nature and is review-based. The thorough literature analysis shows that the curriculum is made up of scriptures that teach about human values and a noble existence. Tarka Shastra, Upanishads, Vedangas, Darshans, Puranas, and four Vedas make up this system. The outcome also shows that Chintan and the oral teaching approach were widely employed. Additional methods of learning included debates, lectures, storytelling, and discussions. Life-related knowledge was given. The investigation revealed that their implementation in the current NEP 2020 will be significant and productive. Life-related learning can be obtained through activities and experiential learning. Experiments will help us understand things better. Schools are able to use oral teaching methods. Sanskrit knowledge is to be taught in schools. Additionally relevant is critical thinking. Regarding the implementation, there are a number of obstacles that must be overcome, including a shortage of funding, government backing, a shortage of qualified teachers, and many more. Therefore, by overcoming them and putting the same into practice, we can provide our children with education that is effective, relevant, engaging, and student-centric.